LA INVESTIGACIÓN EN LA ACADEMIA FACTOR CLAVE PARA SU APORTE AL DESARROLLO NACIONAL - Sánchez Soto, Rubén Gómez (2022)
Peru because of the COVID-19 Pandemic is listed as the country that holds the qualification as the first place due to the resulting economic crisis. It is for this reason that this article addressed the concern and role of the Academy towards national development. According to the investigations carried out, it has been verified that the contribution of the Universities to achieve national development lies in the improvement of human capital; for which, according to the results achieved, the application of the educational model is recommended: Problem/Solution/Product/Project, and direct attention to applied research in the development of its undergraduate and postgraduate courses as a means to specify its contribution to national development.